Platinum nanosheets synthesized via topotactic reduction of single-layer platinum oxide nanosheets for electrocatalysis - Daisuke Takimoto; Shino Toma; Yuya Suda; Tomoki Shirokura; Yuki Tokura; Katsutoshi Fukuda; Masashi Matsumoto; Hideto Imai; Wataru Sugimoto (Nature Communications, 2023)
2D metals are promising electrocatalysts due to their potentially large surface area. Here we report double-layer Pt nanosheets derived from exfoliated PtOx nanosheets with higher electrochemically active surface area, oxygen reduction reaction activity, and stability compared to Pt nanoparticles.